PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE UNTUK MENDORONG PURCHASE DECISION DI EL CRUDO CANGGU - Ni Luh Dian Wulandari; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (VALUES, 2021)
This study aims to analyze the quality of service and store atmosphere of the Purcase Decision. This research was conducted at El Crudo Canggu. The scientific target chosen in this research is in the field of marketing management from El Crudo Canggu. Where the population of this study is all consumers who come to El Crudo Canggu Restaurant with nonprobability sampling sampling technique with the number of samples obtained is 60 respondents. The data used in this study were obtained using the documentation study method, interviews, and questionnaires. In this study, the data analysis technique was used, multiple linear regression analysis to determine the effect of the variables used, and the goodness of fit test. Based on the results of the analysis conducted, it is found that the effect of service quality and store atmosphere on purchase decisions is positive and significant, which means that if the quality of service and store atmosphere increases it will increase the purchase decision of El Crudo Canggu restaurant.